Molecular Modulation of Fetal Liver Hematopoietic Stem Cell Mobilization into Fetal Bone Marrow in Mice - Huihong Zeng; Jiaoqi Cheng; Ying Fan; Yingying Luan; Juan Yang; Feixuan Wang; Shuo Yang; Lijian Shao (Stem Cells International)
Development of hematopoietic stem cells is a complex process, which has been extensively investigated. Hematopoietic stem cells (HSCs) in mouse fetal liver are highly expanded to prepare for mobilization of HSCs into the fetal bone marrow. It is not completely known how the fetal liver niche regulates HSC expansion without loss of self-renewal ability. We reviewed current progress about the effects of fetal liver niche, chemokine, cytokine, and signaling pathways on HSC self-renewal, proliferation, and expansion. We discussed the molecular regulations of fetal HSC expansion in mouse and zebrafish. It is also unknown how HSCs from the fetal liver mobilize, circulate, and reside into the fetal bone marrow niche. We reviewed how extrinsic and intrinsic factors regulate mobilization of fetal liver HSCs into the fetal bone marrow, which provides tools to improve HSC engraftment efficiency during HSC transplantation. Understanding the regulation of fetal liver HSC mobilization into the fetal bone marrow will help us to design proper clinical therapeutic protocol for disease treatment like leukemia during pregnancy. We prospect that fetal cells, including hepatocytes and endothelial and hematopoietic cells, might regulate fetal liver HSC expansion. Components from vascular endothelial cells and bones might also modulate the lodging of fetal liver HSCs into the bone marrow. The current review holds great potential to deeply understand the molecular regulations of HSCs in the fetal liver and bone marrow in mammals, which will be helpful to efficiently expand HSCs in vitro.